2017
DOI: 10.1016/j.ijdevneu.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical biomarkers for diagnosis and therapy monitorization of Niemann‐Pick type C patients

Abstract: Taken together, the present data show that cholestane-3β,5α,6β-triol analysis has a high potential to be an important NP-C screening assay, and also can be used for therapy monitorization with miglustat in NP-C patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Currently, lyso-sphingomyelin-509 (LysoSM-509) is used for the primary diagnosis of Niemann-Pick disease type C [104]. Another biomarker is cholestane-3β,5α,6β-triol [105]. Both biomarkers, however, also accumulate in Niemann-Pick disease types A and B [103].…”
Section: Niemann-pick Disease Type Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, lyso-sphingomyelin-509 (LysoSM-509) is used for the primary diagnosis of Niemann-Pick disease type C [104]. Another biomarker is cholestane-3β,5α,6β-triol [105]. Both biomarkers, however, also accumulate in Niemann-Pick disease types A and B [103].…”
Section: Niemann-pick Disease Type Cmentioning
confidence: 99%
“…Several biomarkers have been investigated for GD, however, none of them is perfect. Chitotriosidase activity levels have been considered as a classic biomarker [105]. They are used as an indicator of disease severity and its response to therapy.…”
Section: Gaucher Diseasementioning
confidence: 99%
“…Oxysterols are formed in the body through enzymatic and non-enzymatic reactions involving reactive oxygen species (ROS). The latter reaction seems to be driving the enhanced levels of oxysterols in NPC [45,46,47,48,49]. Moderate elevation of oxysterol levels is also observed in other cholesterol-related storage diseases, such as atherosclerosis, obesity, and diabetes [50,51,52].…”
Section: Gaucher Cell Biomarkers: Lipidsmentioning
confidence: 99%
“…Additionally, in line with previous reports, cerebrospinal tau proteins were elevated in Case 1 [ 16 ] and the laboratory values of copper metabolism slightly deviated or were close to the lower limit of the normal levels [ 17 ]. Recently, it has been reported that plasma oxysterol (cholestane-3β,5α,6β-triol) is informative in the detection of NPC [ 18 ]. Additionally, lysosphingolipids have been proposed as a potential biomarker for NPC [ 19 ].…”
Section: Discussionmentioning
confidence: 99%